Sodium humate alters the intestinal microbiome, short-chain fatty acids, eggshell ultrastructure, and egg performance of old laying hens - Li, Chenqinyao; Li, Xue; Li, Piwu; Wei, Bin; Zhang, Cong; Zhu, Xiaoling; Zhang, Jie (Frontiers in Veterinary Science, 2022)
This study investigated the effect of sodium humate supplementation on changes in the intestinal microbiome and intestinal short-chain fatty acids production and trace element absorption in older laying hens, with consequent effects on egg performance and shell quality. We used the same hens as their own control, a total of 720 laying hens aged 422 days were randomly divided into three replicates, with the CON group fed a commercial diet at 422-441 days of age and the HANa group fed a commercial diet supplemented with 0.05% sodium humate at 442-461 days of age. Compared with the CON group, in the HANa group, Bacteroidetes and Actinobacteria were a significant increase, and Firmicutes were a significant decrease. Veillonella, Enterococcus, Lactobacillus, and Turricibacter were significant decrease, Peptoniphilus, Helcococcus, GW-34, Psychrobacter, Anaerococcus, Corynebacterium, Facklamia, Trichococcus, Gallicola, Clostridium, and Oscillospira significant increase. The results showed that sodium humate significantly altered the alpha and beta diversity and changed the structure of the intestinal microbiome. Acetic acid, isovaleric acid, and isobutyric acid in short-chain fatty acids were significantly increased in the HANa group, while trace elements such as Mn, Zn, and Fe were significantly reduced. The eggshell strength and ultrastructure were significantly altered. In this study, sodium humate was found to alter the intestinal microbiome structure of aged hens, change the production of short-chain fatty acids, and promote the absorption of trace elements to keep aged hens from experiencing a decrease in egg production performance.